International Experiences of Introducing Dual Training Based on Examples from Some Countries - Toth, Katalin (International Journal of Engineering and Management Sciences, 2022)
In Hungary, dual training was introduced in 2015.  Dual training is a response to the needs of the labour market and has become increasingly popular since its introduction. Dual training is also playing an increasingly important role in higher educationin many countries, helping to modernise education, the knowledge transferred and fostering stronger links between companies and universities. The aim of this article is to present the dual training system and the international experience gained over time, drawing on the literature available on the subject.